Evaluating the impact of education on earnings in the UK: Models, methjods and results from the NCDS - Richard W. Blundell; Lorraine Dearden; Barbara Sianesi (Institute for Fiscal Studies (IFS), 2003)
Regression, matching, control function and instrumental variables methods for recovering the impact of education on individual earnings are reviewed for single treatment and sequential multiple treatments with and without heterogeneous returns. The sensitivity of the estimates once applied to a common dataset is then explored. We show the importance of correcting for detailed test score and family background differences and of allowing for (observable) heterogeneity in returns. We find an average return of 27% for those completing higher education versus anything less. Compared to stopping at 16 without qualifications, we find an average return to O-levels of 18%, to A-levels of 24% and to higher education of 48%.
Keywords: 330; Returns to education; Evaluation; Non-experimental methods; Heterogeneity; Selection; Multiple treatments; Matching; Propensity score; Instrument variables; Control function; Bildungsertrag; Bildungsniveau; Statistische Methode; Bildungsabschluss